Lesional CD4+ IFN-γ+ cytotoxic T lymphocytes in IgG4-related dacryoadenitis and sialoadenitis. Issue 2 (29th June 2016) - Maehara, Takashi; Mattoo, Hamid; Ohta, Miho; Mahajan, Vinay S; Moriyama, Masafumi; Yamauchi, Masaki; Drijvers, Jefte; Nakamura, Seiji; Stone, John H; Pillai, Shiv S
Abstract : Objectives: IgG4-related disease (IgG4-RD) is a chronic, systemic, inflammatory condition of unknown aetiology. We have recently described clonally expanded circulating CD4 + cytotoxic T lymphocytes (CTLs) in IgG4-RD that infiltrate affected tissues where they secrete interleukin (IL)-1β and transforming growth factor -β1 (TGF-β1). In this study, we sought to examine the role of CD4 + CTLs in the pathogenesis of IgG4-related dacryoadenitis and sialoadenitis (IgG4-DS) and to determine whether these cells secrete interferon-gamma (IFN-γ) at lesional sites. Methods: Salivary glands of 25 patients with IgG4-DS, 22 patients with Sjögren's syndrome (SS), 12 patients with chronic sialoadenitis (CS) and 12 healthy controls were analysed in this study. Gene expression analysis was performed on submandibular glands (SMGs) from five patients with IgG4-DS, three with CS and three healthy controls. Infiltrating CD4 + CTLs were examined by quantitative multicolour imaging in tissue samples from 20 patients with IgG4-DS, 22 patients with SS, 9 patients with CS and 9 healthy controls. Results: In IgG4-DS tissues, nine genes associated with CD4 + CTLs were overexpressed. The expression of granzyme A (GZMA) mRNA was significantly higher in samples from patients with IgG4-RD compared with corresponding tissues from SS and healthy controls. Quantitative imaging showed that infiltrating CD4 + GZMA + CTLs were more abundant in patients with IgG4-DS than in the other groups. The ratio of CD4 + GZMA + CTLs in SMGs from patients with IgG4-DS correlated with serum IgG4 concentrations and the number of affected organs. A large fraction of CD4 + GZMA + CTLs in SMGs from patients with IgG4-DS secreted IFN-γ. Conclusions: The pathogenesis of IgG4-DS is associated with tissue infiltration by CD4 + GZMA + CTLs that secrete IFN-γ.